Teaching Statistics in the Health Sciences Resources Portal. Issue 4 (2nd October 2021) - Bigelow, Carol; Nowacki, Amy S.
Abstract : This article describes the American Statistical Association (ASA) Section on Teaching of Statistics in the Health Sciences (TSHS) resources portal (Portal). The Portal is designed specifically for teachers. It is a repository of publicly available, peer-reviewed health sciences related teaching datasets, together with accompanying (vetted) teaching materials that are available to registered instructors. The Portal is simple to use and can be found at https://www.causeweb.org/tshs/